2021
DOI: 10.1007/s11663-021-02213-7
|View full text |Cite
|
Sign up to set email alerts
|

Three-Stage Method Energy–Mass Coupling High-Efficiency Utilization Process of High-Temperature Molten Steel Slag

Abstract: High-temperature molten steel slag is a large amount of industrial solid waste containing available heat energy and resources. This paper introduces an efficient and comprehensive utilization process of high-temperature molten steel slag. The waste heat energy in the high-temperature molten steel slag can be fully recovered through the three-stage heat exchange. Through mass balance and energy balance, the theoretical heat recovery rate can reach 81.42 pct when the waste heat stored in steel slag is converted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…SS is relatively similar in chemical composition to cement and is able to react with water in a hydration process, which has a certain cementitious effect. Although SS is less cementitious than cement, the energy consumption involved in its production is greatly reduced compared to cement [4,5]. Based on previous studies, Rashad [6,7] summarized the application of SS as a binder or aggregates for mortar or concrete and found that the utilization of steel slag could lead to excellent engineering indicators.…”
Section: Introductionmentioning
confidence: 99%
“…SS is relatively similar in chemical composition to cement and is able to react with water in a hydration process, which has a certain cementitious effect. Although SS is less cementitious than cement, the energy consumption involved in its production is greatly reduced compared to cement [4,5]. Based on previous studies, Rashad [6,7] summarized the application of SS as a binder or aggregates for mortar or concrete and found that the utilization of steel slag could lead to excellent engineering indicators.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3–5 ] Therefore, the effective utilization of steel slag is an urgent issue to achieve the emission reduction in metallurgy industry. [ 6–9 ]…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Therefore, the effective utilization of steel slag is an urgent issue to achieve the emission reduction in metallurgy industry. [6][7][8][9] Hot steel slag with temperature over 1773 K carries a lot of high-grade physical heat, and thus adding modifiers into the hot slag to make the slag modification through utilizing waste heat can significantly improve the physicochemical property of hot slag and stabilization of free CaO and MgO, which is needed for the valuable element recycling and steel slag valorization. During the hot slag modification stage, the temperature control of hot slag is one of the major factors contributing towards the modification effect of hot slag.…”
mentioning
confidence: 99%